Relationship between attitude and behavioural intention towards incantation (mantra) in traditional healing among Indian community in Taman Seri Serdang, Selangor - Subramaniam, Vickneswarry (2013)
Although Indians in Malaysia are a minority population, they continue with their traditional beliefs and religious or cultural activities without any obstacle. The aim of this study was to determine the relationship between attitude and behavioural intention towards incantation among the Indian community in Taman Sri Serdang, in the state of Selangor, Malaysia. There are four objectives in this study: (1) to determine levels of knowledge, attitude, subjective norm, perceived behaviour control, and intention towards incantation; (2) to measure the difference in attitude, subjective norm, perceived behaviour control and intention in relation to gender and age towards incantation; (3) to examine relationship between knowledge, attitude, subjective norm, perceived behaviour control, and intention towards incantation and (4) to predict factors that contribute to behavioural intention of the Indian community in Taman Sri Serdang towards incantation. In this study, the Theory of Planned Behaviour (TPB) proposed and developed by Icek Ajzen (Ajzen, 1991) was used. This theory explains the reason why people behave in a certain way in certain situations. This theory explains that people’s behaviour is influenced by their intention to perform a particular action. This theory casts light on behavioural intention, which is determined by attitude, subjective norm and perceived behaviour control. For this purpose, 217 respondents from various backgrounds were identified using a simple random sampling from Taman Sri Serdang. Data were collected using a questionnaire, which, when completed and returned, were analyzed using Statistical Package for Social Science (SPSS) version 19.0. Findings indicate that the knowledge level is high while the level for attitude, subjective norm, perceived behaviour control, and intention towards incantation is moderate. Meanwhile, there is a positive association between attitude and behaviour with respect to gender and age. There is low correlation between subjective norm and intention, moderate correlation between attitude and intention, and high correlation between perceived behaviour control and intention. In conclusion, attitude towards incantation is high but behaviour is moderate towards incantation among the Indian community in Taman Sri Serdang. The factor that contributes to human behaviour is perceived behaviour control. Thus, based on the findings of the study, it is recommended that the government should encourage and approve of this kind of traditional medicine so that there will be awareness and acceptance of this practice in today’s social context.